An overlay network for replica placement within a P2P VoD network. (3rd April 2006) - Wan, Kan Hung; Loeser, Chris
Generic file sharing P2P applications have gained high popularity in the past few years. In particular, P2P streaming architectures have also attracted attention. Many of them consider many-to-one streaming or high-level multicast techniques. In contrast to these models, we propose techniques and algorithms for point-to-point streaming in autonomous systems as it might occur in large companies, a campus or even in large hotels. Our major aim is to create a replica situation that inter-subnetwork RSVP streams are reduced to a minimum. Therefore, we introduce the architecture of an overlay network for interconnecting subnetworks. Each subnetwork contains a so-called local active rendezvous server (LARS), which not only acts as directory server but also controls availability of movie content in its subnetwork. Owing to this, we consider data placement strategies depending on restrictions of network bandwidth, peer capabilities, as well as the movies' access frequency.